Periodontal disease in a Rubinstein–Taybi syndrome patient: case report - N. M. FREITAS, A. V. IMBRONITO, C. S. K. LA SCALA, R. F. M. LOTUFO, & F. E. PUSTIGLIONI (Paediatric Dentistry, 2006)
Rubinstein–Taybi syndrome (RTS) is a rare disorder affecting 1 of 300,000 people, characterized by growth, mental and motor retardation, small stature, broad thumbs and toes, characteristic face, high-arched palate,and recurrent respiratory infections.